2015
DOI: 10.1002/ejlt.201300500
|View full text |Cite
|
Sign up to set email alerts
|

Longer consumption of flaxseed oil enhances n‐3 fatty acid content of chicken meat and expression of FADS2 gene

Abstract: The aim of this study was to evaluate the effect of different durations of flaxseed oil consumption on broiler performance, fatty acid content of meat and expression of FADS2 gene in the liver of chicken. A total of 336 unsexed day old chicks were randomly assigned to 7 dietary treatments with 4 replicates of 12 chickens in each. Body weight, weight gain, feed intake and feed conversion ratio were not affected by dietary treatments. Longer consumption of flaxseed oil resulted in higher deposition of long chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 57 publications
9
22
1
Order By: Relevance
“…In agreement with the results of present study, it has been reported that increasing the duration of flaxseed oil consumption increased the total PUFA level in chicken meat (Crespo and Esteve‐Garcia, ), which might be due to higher de novo synthesis of fatty acids (Smink et al, ). The higher PUFA levels in flaxseed, particularly ω‐3 fatty acids, which undergo faster absorption in the gut without any significant biohydrogenation can be responsible for higher PUFA in meat at the expense of SFA (Mir et al, ; Mirshekar et al, ). The increase in the duration of flaxseed oil feeding in broiler chickens significantly reduced the SFA, palmitic acid, stearic acid, and eicosanoic acid in broiler chicken meat (Mirshekar et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with the results of present study, it has been reported that increasing the duration of flaxseed oil consumption increased the total PUFA level in chicken meat (Crespo and Esteve‐Garcia, ), which might be due to higher de novo synthesis of fatty acids (Smink et al, ). The higher PUFA levels in flaxseed, particularly ω‐3 fatty acids, which undergo faster absorption in the gut without any significant biohydrogenation can be responsible for higher PUFA in meat at the expense of SFA (Mir et al, ; Mirshekar et al, ). The increase in the duration of flaxseed oil feeding in broiler chickens significantly reduced the SFA, palmitic acid, stearic acid, and eicosanoic acid in broiler chicken meat (Mirshekar et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The higher PUFA levels in flaxseed, particularly ω‐3 fatty acids, which undergo faster absorption in the gut without any significant biohydrogenation can be responsible for higher PUFA in meat at the expense of SFA (Mir et al, ; Mirshekar et al, ). The increase in the duration of flaxseed oil feeding in broiler chickens significantly reduced the SFA, palmitic acid, stearic acid, and eicosanoic acid in broiler chicken meat (Mirshekar et al, ). However, in contrast to the current study the decrease of oleic acid and MUFA was also observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular fat (IMF) content of chicken, pork, beef and lamb typically varies between 10-25, 15-40, 20-50 and 30-80 g/kg, respectively (14,15,20,21) . For chicken, the lipid content of dark meat and light meat averages 28 and 11 g/kg, respectively (21)(22)(23)(24)(25)(26) . The IMF of chicken and pork contains 260-350, 290-460 and up to 200 g/100 g, as SFA, MUFA and PUFA, respectively (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) .…”
Section: Lipid In Meat From Monogastric and Ruminant Animalsmentioning
confidence: 99%
“…For chicken, the lipid content of dark meat and light meat averages 28 and 11 g/kg, respectively (21)(22)(23)(24)(25)(26) . The IMF of chicken and pork contains 260-350, 290-460 and up to 200 g/100 g, as SFA, MUFA and PUFA, respectively (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . In beef and lamb, IMF contains 450-480 and 350-450 g/100 g of SFA and MUFA, respectively and up to 50 g/100 g as PUFA, respectively (17,18) .…”
Section: Lipid In Meat From Monogastric and Ruminant Animalsmentioning
confidence: 99%